2011
DOI: 10.1021/jo200869a
|View full text |Cite
|
Sign up to set email alerts
|

Acid–Base Jointly Promoted Copper(I)-Catalyzed Azide–Alkyne Cycloaddition

Abstract: In this novel acid-base jointly promoted CuAAC, the combination of CuI/DIPEA/HOAc was developed as a highly efficient catalytic system. The functions of DIPEA and HOAc have been assigned, and HOAc was recognized to accelerate the conversions of the C-Cu bond-containing intermediates and buffer the basicity of DIPEA. As a result, all drawbacks occurring in the popular catalytic system CuI/NR(3) were overcome easily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
102
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(107 citation statements)
references
References 48 publications
5
102
0
Order By: Relevance
“…As was expected, the reaction of these more sterically hindered azidosteroids proceeded more slowly and proved sensitive to the composition of a catalytic system. The use of CuSO4·5H2O and NaAsc in aqueous THF (method A) allowed them to obtain product 149c (R = Bu) via reaction of azidosteroid 145 with propargyl alcohol, but in the case of phenylacetylene conversion was only 48% after 14 h. Since copper carboxylates are known to accelerate the CuAAC reaction, 58 they applied presumably more active Cu(OAc)2·H2O as a catalyst. Triethylamine was added to increase the solubility of the catalyst in CH2Cl2 and facilitate the formation of copper acetylide.…”
Section: Page 230mentioning
confidence: 99%
“…As was expected, the reaction of these more sterically hindered azidosteroids proceeded more slowly and proved sensitive to the composition of a catalytic system. The use of CuSO4·5H2O and NaAsc in aqueous THF (method A) allowed them to obtain product 149c (R = Bu) via reaction of azidosteroid 145 with propargyl alcohol, but in the case of phenylacetylene conversion was only 48% after 14 h. Since copper carboxylates are known to accelerate the CuAAC reaction, 58 they applied presumably more active Cu(OAc)2·H2O as a catalyst. Triethylamine was added to increase the solubility of the catalyst in CH2Cl2 and facilitate the formation of copper acetylide.…”
Section: Page 230mentioning
confidence: 99%
“…The most common one involves cycloaddition of azides and alkynes in the presence of a catalyst (Rostovtsev et al, 2002;Himo et al, 2005;Boren et al, 2008;Quan et al, 2014;Banday & Hruby, 2014;Kolarovič et al, 2011;Shao et al, 2011;Liu & Reiser, 2011). A number of heterocycles containing the 1,2,3-triazole moiety show various medicinal applications (Bock et al, 2006(Bock et al, , 2007Agalave et al, 2011).…”
Section: Structure Descriptionmentioning
confidence: 99%
“…82,184,185 Additionally, it was recently shown that catalytic amounts of certain acids can further accelerate the formation of the triazole product through promotion of the conversion of C-Cu bond-containing intermediates by protonation. [186][187][188] Furthermore, utilization of acidic additives is beneficial as it prevents the formation of unwanted byproducts, such as diacetylenes, bis-triazoles, etc.…”
Section: Scheme 16 13-dipolar Cycloaddition Between Benzyl Azide Anmentioning
confidence: 99%
“…[186][187][188] Furthermore, utilization of acidic additives is beneficial as it prevents the formation of unwanted byproducts, such as diacetylenes, bis-triazoles, etc. 185 In contrast, byproduct formation is catalyzed by base. The joint application of a basic and an acidic additive is therefore highly advantageous: this buffer system improves reactivity in CuAAC, even at RT, but without the formation of byproducts.…”
Section: Scheme 16 13-dipolar Cycloaddition Between Benzyl Azide Anmentioning
confidence: 99%
See 1 more Smart Citation